Downstream fish passage at small-scale hydropower plants: Turbine or bypass? - Knott, Josef; Mueller, Melanie; Pander, Joachim; Geist, Juergen (Frontiers in Environmental Science, 2023)
Hydropower plants are frequently equipped with physical and behavioral fish protection barriers to prevent downstream moving fish from harmful turbine passage and to guide them to alternative bypasses. As not only diadromous but also potamodromous fish species migrate and inevitably have to pass hydropower plants, knowledge on corridor usage for a wide range of species is important to identify potential deficits and to improve bypass efficiency. In this study, the corridor usage of downstream moving fish (6,646 individuals from 42 species) was investigated at four small-scale hydropower plants with different concepts to prevent turbine entrainment and to bypass fish. Despite existing bypasses and fine screens with 15 mm and 20 mm bar spacing to prevent turbine entrainment, a large proportion of fish (35–88%) still passed the turbines. The mainly poor efficiency of the investigated bypasses was probably due to low discharge and unfavorable bypass location or detectability. The various bypass types were used by a different range of fish species and sizes due to species-specific behavior and differing fish communities between sites. The effectiveness of the investigated downstream corridors was positively correlated with the share of discharge. To reduce the negative ecological impacts of hydropower plants on downstream moving fish, well-performing bypasses are required that consider not only current requirements regarding design, dimensioning and location, but also the site-specific fish community. Thus, bypasses should function for the widest possible range of species, which can be achieved through less selective bypass types such as full-depth bypasses, or a combination of different bypass systems. Moreover, less harmful turbine technologies and more effective fish protection systems need to be implemented, since fine screens with 15 mm and 20 mm bar spacing cannot prevent small-bodied fish species and juvenile fish <20 cm from turbine entrainment.